Conflitos e potencialidades de um território de periferia: análise da percepção socioambiental de moradores do Jardim Gonzaga, São Carlos, SP, Brasil - Faraco, Rafaela Maria Briso (2012)
The brazillian fast and disorderly process of urbanization has led to inadequate suburbs and occupations in areas of environmental value. This logic is common to large and mediumsized cities, as São Carlos town, where is located the Jardim Gonzaga, a pocket of poverty in the border of the urban area characterized by informal land use , lack of infrastructure and the prevalence of substandard housing, with high social and environmental vulnerability. For this reason, a set of public character and local development programs were implemented in Jardim Gonzaga. In this context, the objective of this paper is to analyze and understand the social and environmental perception of Jardim Gonzaga’s residents about the life quality and environment, especially emphasizing aspects of sanitation, housing, health, green and recreational areas. Methodologically, the study included literature review, social and environmental diagnostics, systematic observation and interviews with local residents. The results indicate that environmental conflicts are related to: the lack of green areas and recreation, solid waste disposal, the macro drainage problems and the irregular release of sewage into conservation areas. Residents recognize some public programs to revitalize urban areas and have greater identification with the environmental projects developed by NGO’s and Universities. There is a need for actions that integrate the residents, the Community Station, the residents' association, the government and other institutions to foster effective actions and recognized by local people so that they can actually contribute to increase the life quality and environment.